2021
DOI: 10.3928/01913913-20201007-01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Gaze Fixation Position on AS-OCT Measurements of the Limbus and Extraocular Muscle Insertion Site Distance

Abstract: Purpose: To investigate the effect of the gaze fixation position on measurement of the limbus and extraocular muscle (EOM) insertion site distance using anterior segment optical coherence tomography (AS-OCT). Methods: Patients undergoing horizontal EOM surgeries were enrolled in this prospective experimental study. The distance between the angle recess and the muscle insertion site was measured using AS-OCT while patients fixed their gaze laterally or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Our analysis found that the distance between the MR insertion location and the limbus, as well as the distance between the LR insertion location and the limbus, did not differ significantly in Taiwanese patients compared with East and Southeast Asian patients (Chinese, Japanese, and Thai, as shown in Supplementary Table of Supporting information S1). 2,3,14 However, we observed that the distance from the MR insertion location to the limbus was significantly longer in Koreans compared with Taiwanese 15 . On the other hand, the distances from the MR and LR insertion locations to the limbus were shorter in Taiwanese patients compared with Indian, Polish, and Turkish patients 4,16,17 .…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Our analysis found that the distance between the MR insertion location and the limbus, as well as the distance between the LR insertion location and the limbus, did not differ significantly in Taiwanese patients compared with East and Southeast Asian patients (Chinese, Japanese, and Thai, as shown in Supplementary Table of Supporting information S1). 2,3,14 However, we observed that the distance from the MR insertion location to the limbus was significantly longer in Koreans compared with Taiwanese 15 . On the other hand, the distances from the MR and LR insertion locations to the limbus were shorter in Taiwanese patients compared with Indian, Polish, and Turkish patients 4,16,17 .…”
Section: Discussionmentioning
confidence: 64%
“…4,16,17 Hence, populations from different countries living in geographically close regions may have similar EOM insertion locations. [2][3][4]6,[14][15][16][17][18] As mentioned in the introduction, differences in surgical outcome were believed to be due to differences in surgical conditions and surgeons' technique. However, this study shows that surgical dosages may need to be adjusted not only among different surgeons, but also among different countries.…”
Section: Comparison Of Postoperative Deviations Between Original and ...mentioning
confidence: 99%
See 3 more Smart Citations